The impact of public health expenditure and gross domestic product per capita on the risk of catastrophic health expenditures for OECD countries - Söyük, Selma (Frontiers in Public Health, 2023)
Introduction Catastrophic health expenditure refers to situations where households face financial ruin due to high healthcare costs. For household spending on health services, the lack of pre-payment mechanisms to equalize the low payment capacity and risk, and the inability of countries' health financing systems to fulfill their duties adequately all contribute to the creation or increase of the risk of catastrophic health expenditure. This situation has devastating effects on poor households first, but if the prevention mechanisms are insouciant, it can threaten the health system of the entire country. The research aims to assess the impact of the pre-paid financing model implementations and income levels on the ability of countries to reduce the risk of catastrophic health expenditure. Methods The paragraph explains the data used in the study, which is taken from OECD countries between 2003 and 2019. It also mentions the statistical models used in the study, which are static and dynamic panel regression models. Results The findings indicate that pre-paid financing models, such as those based on taxation, can help reduce the risk of catastrophic health expenditure. The study also reveals that income levels play a role in this regard, with countries with higher incomes being better able to reduce the risk of catastrophic health expenditure. Discussion The study suggests that healthcare financing systems should aim to provide effective services and financial protection to improve universal health coverage and reduce the risk of catastrophic health expenditure. Further researches using different health indicators and inputs could add to the existing literature on how to limit catastrophic health expenses and address other related questions.